Equatorial wrinkles in the human lens capsule - Burd, H; Montenegro, G; Cortés, L; Barraquer, R; Michael, R (Elsevier, 2017)
Equatorial wrinkles, or crenations, have been previously observed around the equator in coronal images of the human ocular lens. However, wrinkles are typically not apparent when the lens is viewed from saggital directions. In the current paper, the existence and geometry of these wrinkles is shown to be consistent with a mechanical model of the isolated lens, in which the capsule is held in a state of residual tension by a spatially uniform internal pressure. The occurrence of equatorial wrinkles is therefore seen to be a mechanical consequence of the spheroidal shape of the lens capsule and an excess intralenticular pressure. New observations are made, on post mortem lenses, on the geometric arrangement of these equatorial wrinkles. These observations indicate a well-defined pattern in which wrinkles exists along meridional lines in the equatorial regions of the lens. A preliminary 'puncture test' is used to demonstrate that the residual stresses within the capsule in the equatorial region of the lens are broadly consistent with the proposed mechanical model of the lens capsule. It is suggested that the presence of equatorial wrinkles may have an influence on the mechanical performance of the capsule during the accommodation process.